2019
DOI: 10.1186/s12866-019-1552-1
|View full text |Cite
|
Sign up to set email alerts
|

Change of intestinal microbiota in cerebral ischemic stroke patients

Abstract: Background Gut microbiota has been suggested to play a role in stroke patients. Nevertheless, little is known about gut microbiota and the clinical indexes in stroke patients. Methods Total of 30 cerebral ischemic stroke (CI) patients and 30 healthy control were enrolled in this study and the fecal gut microbiota was profiled via Illumina sequencing of the 16S rRNA V1-V2. The National Institutes of Health Stroke Scale (NIHSS) were used to quantify stroke severity and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
202
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(236 citation statements)
references
References 30 publications
11
202
2
Order By: Relevance
“…However, these results may be confounded by factors, such as age, type 2 diabetes mellitus or obesity, which are risk factors for stroke that are associated with a different gut microbiota composition (Qin et al, 2012;Karlsson et al, 2013;Torres-Fuentes et al, 2017;An et al, 2018). For αdiversity, studies are also contradictory (Yin et al, 2015;Li N. et al, 2019). Furthermore, decreased neuronal injury and improved cognitive performance was observed in diabetic mice with bilateral common carotid arteries occlusion after receiving Clostridium butyricum suspension intragastrically (Sun et al, 2016).…”
Section: Role Of the Gut Microbiota In Disease Symptoms And Pathogenesismentioning
confidence: 99%
“…However, these results may be confounded by factors, such as age, type 2 diabetes mellitus or obesity, which are risk factors for stroke that are associated with a different gut microbiota composition (Qin et al, 2012;Karlsson et al, 2013;Torres-Fuentes et al, 2017;An et al, 2018). For αdiversity, studies are also contradictory (Yin et al, 2015;Li N. et al, 2019). Furthermore, decreased neuronal injury and improved cognitive performance was observed in diabetic mice with bilateral common carotid arteries occlusion after receiving Clostridium butyricum suspension intragastrically (Sun et al, 2016).…”
Section: Role Of the Gut Microbiota In Disease Symptoms And Pathogenesismentioning
confidence: 99%
“…Interestingly, changes in some Ruminococcaceae have been associated with behavioral deficits and social avoidance in mice [74,75]. Human fecal samples taken from stroke patients within 48 hours of hospital admission showed an increase in Ruminococcaceae_UCG_005; and three genera of Ruminococcaceae were consistently upregulated in severe stroke compared to mild stroke patients [76]. The abundance of Ruminococcaceae in neurocritically ill patients has been negatively associated with length of hospital stay [77].…”
Section: Cells and Significant Increases In Cd4+ T Cells And Cd8+ Tmentioning
confidence: 99%
“…Related studies have shown that post-stroke inflammatory response is a long-lasting pathological process of ischemic brain injury, which is an important cause of secondary brain injury 4) . This process is closely related to intestinal microbial imbalance and intestinal barrier destruction after stroke [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%